Development and equality evaluation of millet fortified tuber based extruded RTE products - SEEMA B.R; Dr. Sudheer K.P (Guide) (Tavanur 2016 Department of Food and Agricultural Process Engineering)
Development and equality evaluation of millet fortified tuber based extruded RTE products
Development and equality evaluation of millet fortified tuber based extruded RTE products